Effect of the association of nystatin with a tissue conditioner on its ultimate tensile strength - Urban, Vanessa Migliorini [UNESP]; De Souza, Raphael Freitas; Galvao Arrais, Cesar Augusto; Borsato, Karina Tostes [UNESP]; Vaz, Luis Geraldo [UNESP] (Wiley, 2006)
Purpose: This study evaluated the ultimate tensile strength of a tissue conditioner without nystatin incorporation (GI - control group) and the same tissue conditioner modified by the addition of nystatin in two concentrations: GII - 500,000 International Units (U) and GIII - 1,000,000 U, in which each milligram of the medicament corresponded to 6079 U. Materials and Methods: Dumbbell-shaped specimens (N = 7) with a central cross-sectional area of 33 × 6 × 3 mm were produced for the three experimental groups. After polymerization following manufacturer's instructions, specimens were immersed in distilled water at 37°C for either 24 hours or 7 days and then tested in tension in the MTS 810 at 40 mm/minute. Data were analyzed by two-way ANOVA followed by Tukey's test, at 95% level of confidence. Results: The means (force-grams (gf) ± standard deviation) of the ultimate tensile strength were: GI - 634.29 ± 122.80; GII - 561.92 ± 133.56; and GIII - 547.30 ± 73.47 for 24-hour storage, and GI - 536.68 ± 54.71; GII - 467.50 ± 143.51; and GIII - 500.62 ± 159.76 for 7-day storage. There were no statistically significant differences among the three experimental groups (p > 0.05). The ultimate tensile strength means of all experimental groups after 7 days were significantly lower than those observed after 24 hours (p = 0.04). Conclusions: The results of this study suggest that the addition of nystatin into the tissue conditioner investigated in concentrations below 1,000,000 U did not affect its ultimate tensile strength. Copyright © 2006 by The American College of Prosthodontists.
Keywords: Antifungal agent; Candida albicans; Denture stomatitis; UTS; alcohol; antifungal agent; methacrylic acid methyl ester; nystatin; phthalic acid dibutyl ester; plasticizer; analysis of variance; dental care; denture; drug storage; materials testing; reparative dentistry; stomatitis; tensile strength; thrush; time; Analysis of Variance; Antifungal Agents; Candidiasis, Oral; Dental Stress Analysis; Denture Liners; Dibutyl Phthalate; Drug Storage; Ethanol; Materials Testing; Methylmethacrylate; Nystatin; Plasticizers; Stomatitis, Denture; Tensile Strength; Time Factors; Tissue Conditioning (Dental)